Lifestyle and Metabolic Determinants of Incident Hypertension, With Special Reference to Cigarette Smoking: A Longitudinal Population-Based Study - Onat, Altan; Ugur, Murat; Hergenc, Guelay; Can, Guenay; Ordu, Serkan; Dursunoglu, Dursun (OXFORD UNIV PRESS, 2009)
BACKGROUND Lifestyle and metabolic determinants of incident hypertension in a population with a high prevalence of metabolic syndrome (MetS) need to be further assessed. METHODS A representative sample of middle-aged and elderly Turkish adults was prospectively evaluated over a mean 7.4 years, after exclusion of prevalent hypertension and major renal dysfunction. RESULTS In 2,427 men and women, aged 45.8 +/- 11.7 years, Kaplan-Meier analysis showed in combined genders mean time to incident hypertension to be 7.23 years in never, 7.78 years in current smokers (P < 0.001). Age and female sex were major determinants of subsequent hypertension after adjustment for physical activity grade, family income bracket, smoking status, usage of alcohol and of hormone replacement or birth control pill. Relative risk (RR) for incident hypertension of current vs. never smoking was reduced in women (P = 0.058) and both genders combined (P = 0.054). Former smokers uniformly exhibited significantly higher risk for the development of hypertension than both never (P = 0.054) and current (P < 0.001) smokers, whereby abdominally obese individuals were at increased risk. In further multivariable models, circulating C-reactive protein (CRP) and fasting insulin emerged as modest independent determinants and waist girth, modulated by current smoking, as a major determinant of subsequent hypertension. CONCLUSIONS Age, female sex, and waist circumference are major and serum insulin and CRP modest determinants of incident hypertension in middle-aged Turkish adults in whom current cigarette smoking plays a protective role at borderline significance, largely by modulating waist girth. Former smokers with abdominal obesity are under higher risk of subsequent hypertension than current smokers.
Keywords: BLOOD-PRESSURE; ABDOMINAL OBESITY; FOLLOW-UP; WAIST CIRCUMFERENCE; CARDIOVASCULAR RISK; INSULIN-RESISTANCE; TURKISH WOMEN; MEN; ASSOCIATION; DEFINITION; Cardiovascular System & Cardiology